Perbedaan Bentuk Kejahatan Yang Dikategorikan Sebagai Cyber Crime Dan Cyber Warfare - Indah Sari (Fakultas Ilmu Komputer dan Desain - Unsurya, 2023)
The reason behind this writing is based by the development of technology which plays significant role in daily life. Computer device and internet have become important thing for countryâ€™s life, enable them to conquer, control, and observe every human movement in other world. Computer device and internet have created a new world called cyberspace. Along with the progress of cyberspace, it also develops many lawbreaking actions that based with computer device and internet, some of them are cyber crime and cyber warfare. From this background, the writer elevates two problem from this case. First, what form of crime that can be categorized as cyber crime and cyber warfare? Second, how to protect ourselves from the threat of cyber crime and cyber warfare? The kind of typing that the writer uses in this research is descriptive research (describing an object and taking simple conclusion from it) with secondary data and use statute approach, case approach, and conceptual approach. This kind of technique is collected by library researchÂ and the data will be analyzed qualitatively. As for the study result, it consists of: the writer found many different form between cyber crime and cyber warfare. Example of cyber crime are Unauthorized Access to Computer System and Service, Illegal Contents, Data Forgery, Cyber Espionage, Cyber Sabotage and Extortion, Offence Against Intellectual Property, and Infringements of Privacy, while the example of cyber warfare are spionase cyber, vandalism, sabotage, and power grid hacking. In this report, the writer also explain some tips to defend yourself from the threat of cyber crime and cyber warfare.